Caution: Predictors ahead. Issue 4 (19th October 2018) - Balter, Stephen; Moses, Jeffrey W.
Key Points: Radiation dose data can be used as a starting point to establish local TAVR reference levels. Cancer risk is of concern but is very low in the context of TAVR patients. Improvements in clinical radiation management will reduce both patient and staff risk for all procedures.